Waste management: relevance to environmental sustainability. (10th April 2019) - Abila, Beatrice; Kantola, Jussi
Waste generation and its management present universal challenges related to negative impacts on the environment. Municipal solid waste generation in large quantities on daily basis constitutes serious environmental problems. This paper presents a review of extant literature in the management of municipal waste across a range of countries alongside waste management hierarchy that guide legislations and policies for developed and developing countries. This paper assesses the environmental consequences emanating from the influence of either the presence or absence of contaminants-based diverse management options for municipal solid waste; thereby facilitating policy makers and waste management companies informed choice(s) for the management of municipal waste sustainably. The outcome from the evaluation of environmental effect reveals that incineration; the most common waste-to-energy implementation for municipal solid waste is accompanied with the emission of greenhouse gases, Nitrogen oxides, ammonia, sulphur dioxide contributing to climate change and air acidification. Environmental concern is a critical indicator for determining the best appropriate waste management option(s). The need to encourage the increasing recycling of municipal solid waste to facilitate a global sustainable environment as well as boosting the circular economy and green cities is recommended.